Students’ mathematical reasoning ability in solving TIMSS cognitive domain on Algebraic based on students’ thinking style - Fauziah; Ilham Minggi; Ahmad Talib (Lembaga Penelitian dan Pengembangan Teknologi dan Rekayasa, Yayasan Ahmar Cendekia Indonesia, 2021)
This study aims to describe the students' mathematical reasoning abilities in solving TIMSS cognitive domain reasoning problems in algebraic content in terms of the student’s thinking style of the students. The type of research is a qualitative research study with a descriptive approach. The subjects of this research consisted of one student who representing each of the concrete sequential thinking styles. The instrument of this research used consisted of thinking style questionnaires, mathematical reasoning ability test questions, and interview guidelines. The results of this study indicate that: SK thinking style subjects are able to meet four indicators of mathematical reasoning ability, namely: a) the ability to make guesses, b) the ability to draw conclusions, arrange evidence, provide reasons or evidence for the truth of the solution, c) the ability to draw the validity of an argumen, and d) the ability to find patterns or the nature of mathematical symptoms to make generalizations.